Suppressing the P2-O2 Phase Transition of Na0.67Mn0.67Ni0.33O2 by Magnesium Substitution for Improved Sodium-Ion Batteries - Wang, Peng-Fei; You, Ya; Yin, Ya-Xia; Wang, Yue-Sheng; Wan, Li-Jun; Gu, Lin; Guo, Yu-Guo (Angewandte Chemie International Edition, 2016)
Room‐temperature sodium‐ion batteries (SIBs) have shown great promise in grid‐scale energy storage, portable electronics, and electric vehicles because of the abundance of low‐cost sodium. Sodium‐based layered oxides with a P2‐type layered framework have been considered as one of the most promising cathode materials for SIBs. However, they suffer from the undesired P2–O2 phase transition, which leads to rapid capacity decay and limited reversible capacities. Herein, we show that this problem can be significantly mitigated by substituting some of the nickel ions with magnesium to obtain Na0.67Mn0.67Ni0.33−xMgxO2 (0≤x≤0.33). Both the reversible capacity and the capacity retention of the P2‐type cathode material were remarkably improved as the P2–O2 phase transition was thus suppressed during cycling. This strategy might also be applicable to the modulation of the physical and chemical properties of layered oxides and provides new insight into the rational design of high‐capacity and highly stable cathode materials for SIBs. The P2–O2 phase transition in P2‐Na0.67Mn0.67Ni0.33−xMgxO2 can be effectively suppressed by substituting some of the nickel ions with magnesium. Both the reversible capacity and the capacity retention of this cathode material were thus remarkably improved, and the various phases were characterized by scanning tunneling electron microscopy with atomic resolution.